Adverbs Of Verbs In The Kaili Language, Ledo Dialect: A Study Of Structure And Semantics - Rizki, Rizki; Mohammad Tahir; Syamsuddin, Syamsuddin (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study aims to examine the structure and semantic aspects of verbal adverbs in in the Kaili language, Ledo dialect (BKDL). Verbal adverbs are syntactic elements that function to limit, clarify, or emphasize the meaning of verbs in speech. This study is in the field of morphosyntax and regional language semantics. This study uses a qualitative descriptive approach with observation and conversation as data collection techniques. The analysis was conducted using matching and distributional methods to examine the morphological and syntactic structure, as well as a semantic approach to interpret the lexical and grammatical meanings of BKDL verb adverbs. The results show that morphologically, BKDL verb adverbs are divided into basic forms (monomorphemic) and derivative forms (polymorphemic), which are formed through affixation such as the prefixes {ma-}, {na-}, {mpa-}, {mpo-}, {njam-}, {njuma-}, suffixes {-na}, {-pa}, and confixes {ka-…-na} and reduplication can be pure reduplication (without affixes) or affixed reduplication, either with the addition of prefixes, suffixes, or confixes. The affixed reduplication forms in the BKDL data vary, including: prefix {ma-}/{na-} + basic reduplication (RD); prefix {njuma-} + RD; prefix {mpaka-}/{mpa-} /{mpe-} + RD; RD + suffix {-na}; prefix {ma-} + RD + suffix {-na}; as well as the prefix {ka- } + RD + suffix {-na }. Syntactically, verbal adverbs occupy the left position, right position, and free position in accompanying verbs at the phrase level. Semantically, ten types of meanings were found, namely quality, quantity, limitation, frequency, temporality, manner, negation, necessity, expectation, and uncertainty. This study fills a gap in the study of BKDL verb adverbs, which have not been extensively researched in terms of structure and semantics. These findings contribute to the systematic and scientific preservation and documentation of the richness of regional languages.